Digital Lending and Over-Indebtedness Risk: Evidence from Indonesian MSMEs - Rusnathul Amiah; Muhammad Saleh; Ilham Safar (Universitas Riau Kepulauan, 2026)
This study aims to examine the serial mediation role of business financial pressure and over-indebtedness risk in transmitting the effect of digital lending characteristics on MSME business survival. A quantitative explanatory design was employed with 200 MSME operators who actively use digital lending products, sampled through purposive sampling. Data were analyzed using PROCESS Macro Model 6 with 10,000 bootstrap subsamples and a 95% confidence interval. Results indicate that digital lending characteristics significantly exacerbate business financial pressure, which in turn drives over-indebtedness risk, while the direct effect on business survival is fully absorbed by the mediation chain. Serial mediation is confirmed as significant (IE3 = 0.335; 95% CI [0.231, 0.458]), with the two-stage sequential pathway emerging as the dominant transmission mechanism, surpassing both single-mediator paths. These findings support Debt Trap Theory and Pecking Order Theory, demonstrating that the harm of digital lending operates progressively rather than directly. Effective policy interventions should target both platform design regulation and structural improvements to MSME access to formal financing.